2009
DOI: 10.1111/j.1472-4669.2009.00218.x
|View full text |Cite
|
Sign up to set email alerts
|

Haloarchaeal diversity in 23, 121 and 419 MYA salts

Abstract: DNA was extracted from surface-sterilized salt of different geological ages (23, 121, 419 million years of age, MYA) to investigate haloarchaeal diversity. Only Haloarcula and Halorubrum DNA was found in 23 MYA salt. Older crystals contained unclassified groups and Halobacterium. The older crystals yielded a unique 55-bp insert within the 16S rRNA V2 region. The secondary structure of the V2 region completely differed from that in haloarchaea of modern environments. The DNA demonstrates that unknown haloarchae… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
42
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(43 citation statements)
references
References 38 publications
1
42
0
Order By: Relevance
“…There are several highly cited and critically debated reports of bacterial DNA or cells that have apparently survived for many millions of years enclosed in rock salt (e.g., Vreeland et al 2000, Hebsgaard et al 2005, Park et al 2009 or in amber (Cano & Borucki 1995). In the latter observations, it is striking that the isolated organisms were endospore formers.…”
Section: Age and Agingmentioning
confidence: 94%
“…There are several highly cited and critically debated reports of bacterial DNA or cells that have apparently survived for many millions of years enclosed in rock salt (e.g., Vreeland et al 2000, Hebsgaard et al 2005, Park et al 2009 or in amber (Cano & Borucki 1995). In the latter observations, it is striking that the isolated organisms were endospore formers.…”
Section: Age and Agingmentioning
confidence: 94%
“…[15][16][17][18][19]). Sophisticated sterilization protocols have been developed to exclude that the isolated strains might have been contaminations with present-day haloarchaea.…”
Section: Survival Over Geological Timesmentioning
confidence: 97%
“…We previously showed that the high halide concentration in the cytoplasm of H. salinarum was a major factor in protecting its macromolecules against the oxidative effects of IR (34) and resulted directly from its adaptation to a high-salt environment. H. salinarum is found in hypersaline pools, where it is subjected to cycles of desiccation and rehydration (15), and halophiles have been shown to survive extended periods of time encased inside salt crystals (42). The adaptation of H. salinarum to desiccation is another example of the link between IR resistance and desiccation that has been reported for D. radiodurans and other dry-climate-adapted bacteria (20,38,45) and for some lower eukaryotes, such as rotifers and tardigrades (22,26).…”
Section: Discussionmentioning
confidence: 99%